Toward the Sustainable Development Goals: an integrated assessment of municipal solid waste and carbon emissions for Malaysia’s sustainable municipal solid waste management - Nazibudin, Nazatul Akmal; Abd Manaf, Latifah; Yacob, Mohd Rusli; Zainordin, Nazatul Syadia (Springer, 2026)
Malaysia’s municipal solid waste generation has increased due to population expansion, economic growth, and rapid urbanisation, posing serious management and environmental challenges. This study assesses municipal solid waste trends, composition, and management, and estimates associated carbon emissions from disposal strategies. While the correlation and regression analyses examined the driving factors of generation, methane emissions from landfills are estimated using the 2006 IPCC Tier 2 First Order Decay model. Generation of municipal solid waste is significantly correlated with population and gross domestic product with (r = 0.893, p < 0.001) and (r = 0.755, p < 0.001) respectively. Meanwhile, urbanization rate is correlated weakly (r = 0.338, p = 0.002). The largest composition of municipal solid waste continues to be organic waste (35.5%), with a considerable rise in plastic waste (26.9%). For emissions of methane, the reported values rise from 1.47 Mt CO2-eq yr− 1 in 2000, to 10.65 Mt CO2-eq yr− 1. This highlights the severe climate consequences of reliance on landfilling for Malaysia’s municipal solid waste system. This study highlights to reduce this dependence on landfilling and to push forward with circular economy approaches to reduce emissions. By coordinating municipal solid waste management strategies with climate objectives, the study provides evidence to help bolster national policy and to help meet the United Nations Sustainable Development Goals, specifically SDG 12 (Responsible Consumption and Production) and SDG 13 (Climate Action).